Pengaruh Komunikasi Interpersonal, Kepemimpinan Transformasional dan Komitmen Organisasi Terhadap Kinerja Pengurus PMII Rayon Al-Farabi - Hofifatul Musyarrofah; Eka Farida; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study’s goal was to ascertain the impact of interpersonal communication, transformational leadership and organizational commitment on the performance of PMII Rayon Al-Farabi. The study’s methodology is explanatory research with a quantitative approach. 63 respondents made up the sample in this study, which used the proportionate random sampling method. The results showed that the results of the F test of interpersonal communication, transformational leadership and organizational commitment simultaneously had a significant effect on performance. From the results of the t-test analysis, it is known that the interpersonal communication variable has a significant effect on performance and transformational leadership and organizational commitment variable has not significant effect on performance. Keywords: Interpersonal Communication, Transformational Leadership, Organizational Commitment and Performance